In situ segregation of cobalt nanoparticles on VN nanosheets via nitriding of Co2V2O7 nanosheets as efficient oxygen evolution reaction electrocatalysts. (April 2017) - Peng, Xiang; Wang, Lei; Hu, Liangsheng; Li, Yong; Gao, Biao; Song, Hao; Huang, Chao; Zhang, Xuming; Fu, Jijiang; Huo, Kaifu; Chu, Paul K.
Abstract: Metallic Cobalt nanoparticles segregated in situ on conductive vanadium nitride (Co/VN) nanosheets synthesized by ammonia nitridation of hydrothermally prepared Co2 V2 O7 nanosheets are investigated as high-performance oxygen evolution reaction (OER) electrocatalysts. The metallic Co nanoparticles with a large number of exposed active sites are distributed uniformly and adhere firmly to the VN substrate to enhance the OER efficiency, facilitate fast charge transfer, and improve the stability. As a result, a small overpotential of 320 mV is required to achieve a current density of 10 mA cm −2 with a small Tafel slope of 55 mV dec −1 . The excellent stability is indicated by an overpotential shift of only 34 mV after 2000 cyclic voltammetry cycles at a large current density of 200 mA cm −2 . The precious-metal-free Co/VN nanosheets deliver outstanding OER performance and are promising as electrocatalysts in water splitting and related applications. Graphical abstract: Highlights: Metallic Co nanoparticles segregated in situ on the conductive VN nanosheets. Co nanoparticles distribute uniformly and adhere firmly to the VN substrate. Small charge transfer resistance between Co and VN to facilitate OER kinetics. Strong adhesion between Co and VN prevents Co from falling off and aggregation. The electrocatalyst presents low overpotential, small tafel slope and long lifetime.